Kemični motilci endokrinega sistema - Gramec, Darja (Farmacevtski vestnik, 2019)
Various compounds of both natural and synthetic origin can interfere with endocrine system and consequently adversely affect human health. Exposure to endocrine disruptors is associated with numerous common diseases, such as obesity, diabetes, cardiovascular diseases, infertility in women and men, and cancer. Endocrine disruptors can exert their effects through different mechanisms: (i) they interfere with synthesis, metabolism, transport or elimination of endogenous hormones; (ii) they are agonists or antagonists of selected endocrine receptors, or (iii) bind to membrane receptors and cause nongenomic effects. In this review article, influences of endocrine disruptors, predominantly active substances, on estrogen, androgen, thyroid and glucocorticoid systems will be presented together with their impact on human health.
Keywords: androgeni receptor; endokrini sistem; estrogenski receptor; motilci endokrinega sistema; učinkovine